Frontispiece: In Situ Solid‐State Reactions Monitored by X‐ray Absorption Spectroscopy: Temperature‐Induced Proton Transfer Leads to Chemical Shifts. Issue 44 (11th December 2015) - Stevens, Joanna S.; Walczak, Monika; Jaye, Cherno; Fischer, Daniel A.
Abstract : X‐ray Absorption Spectroscopy In many chemical and biological processes, proton transfer plays a crucial role by impacting the electronic structure and functional properties of materials. Direct evidence of a proton transfer within the solid state is captured by chemical shifts in X‐ray absorption spectroscopy (XAS) in the Communication by J. S. Stevens et al. onpage 15600 ff. Heating of the squaric acid/4, 4′‐bipyridine system leads to a dramatic, rapid phase and colour transition through a cascading Brønsted acid‐base reaction, showcasing XAS as an unambiguous identifier for proton transfer without the need for a priori information and the ability to monitor organic reactions in situ.